2009
DOI: 10.1177/1753193409339941
|View full text |Cite
|
Sign up to set email alerts
|

Casting versus percutaneous pinning for extra-articular fractures of the distal radius in an elderly chinese population: a prospective randomised controlled trial

Abstract: We carried out a prospective randomised controlled clinical trial to compare the functional and radiological outcomes of casting with percutaneous pinning in treating extra-articular distal radial fracture in an elderly Chinese population. Sixty patients were randomly allocated by sealed envelopes to either a 'Cast' group (n = 30) or a 'K-wire' group (n = 30). All patients were available for final follow-up assessment. The radiological outcomes in terms of dorsal angulation, radial inclination and radial lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 24 publications
1
37
0
1
Order By: Relevance
“…These were the three studies with the shortest follow up and the fewest patients. Another later randomised study also found no advantage from pinning [19].…”
Section: Discussionmentioning
confidence: 95%
“…These were the three studies with the shortest follow up and the fewest patients. Another later randomised study also found no advantage from pinning [19].…”
Section: Discussionmentioning
confidence: 95%
“…43 There are few disadvantages of percutaneous pinning like the fear of pin tract infection, besides another minor procedure is required for their removal. 44 Randomised trials [45][46][47] and a systematic review 48 showed that percutaneous pinning across fractures was associated with improved anatomical outcome and minor complications compared with casting. The improved radiological outcomes did …”
Section: 37mentioning
confidence: 99%
“…Maintenance of satisfactory alignment is difficult. 6,7,8,9 Recent studies indicate high rate of re-displacement, reangulation and remanipulation following closed reduction and cast immobilization. 8,9 Supplementary percutaneous K-wire fixation resulted in a significantly better maintenance of the alignment of the completely displaced fractures of the distal radius.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,8,9 Recent studies indicate high rate of re-displacement, reangulation and remanipulation following closed reduction and cast immobilization. 8,9 Supplementary percutaneous K-wire fixation resulted in a significantly better maintenance of the alignment of the completely displaced fractures of the distal radius. [10][11][12][13][14][15] Complications are known to occur in both the groups 13,14 (close reduction and cast immobilisation and close reduction and k-wiring).…”
Section: Introductionmentioning
confidence: 99%